The first samples from Almahata Sitta showing contacts between ureilitic and chondritic lithologies: Implications for the structure and composition of asteroid 2008 TC3. (15th October 2019) - Goodrich, Cyrena Anne; Zolensky, Michael E.; Fioretti, Anna Maria; Shaddad, Muawia H.; Downes, Hilary; Hiroi, Takahiro; Kohl, Issaku; Young, Edward D.; Kita, Noriko T.; Hamilton, Victoria E.; Riebe, My E. I.; Busemann, Henner; et al.
Abstract: Almahata Sitta (AhS), an anomalous polymict ureilite, is the first meteorite observed to originate from a spectrally classified asteroid (2008 TC3 ). However, correlating properties of the meteorite with those of the asteroid is not straightforward because the AhS stones are diverse types. Of those studied prior to this work, 70–80% are ureilites (achondrites) and 20–30% are various types of chondrites. Asteroid 2008 TC3 was a heterogeneous breccia that disintegrated in the atmosphere, with its clasts landing on Earth as individual stones and most of its mass lost. We describe AhS 91A and AhS 671, which are the first AhS stones to show contacts between ureilitic and chondritic materials and provide direct information about the structure and composition of asteroid 2008 TC3 . AhS 91A and AhS 671 are friable breccias, consisting of a C1 lithology that encloses rounded to angular clasts (<10 μm to 3 mm) of olivine, pyroxenes, plagioclase, graphite, and metal‐sulfide, as well as chondrules (~130–600 μm) and chondrule fragments. The C1 material consists of fine‐grained phyllosilicates (serpentine and saponite) and amorphous material, magnetite, breunnerite, dolomite, fayalitic olivine (Fo 28‐42), an unidentified Ca‐rich silicate phase, Fe, Ni sulfides, and minor Ca‐phosphate and ilmenite. It has similarities to CI1 but shows evidence of heterogeneous thermal metamorphism. Its bulk oxygen isotope composition (δ 18 O = 13.53‰, δ 17 O = 8.93‰) is unlike that of any known chondrite, but similar to compositions of several CC‐like clasts in typical polymict ureilites. Its Cr isotope composition is unlike that of any known meteorite. The enclosed clasts and chondrules do not belong to the C1 lithology. The olivine (Fo 75‐88), pyroxenes (pigeonite of Wo ~10 and orthopyroxene of Wo ~4.6), plagioclase, graphite, and some metal‐sulfide are ureilitic, based on mineral compositions, textures, and oxygen isotope compositions, and represent at least six distinct ureilitic lithologies. The chondrules are probably derived from type 3 OC and/or CC, based on mineral and oxygen isotope compositions. Some of the metal‐sulfide clasts are derived from EC. AhS 91A and AhS 671 are plausible representatives of the bulk of the asteroid that was lost. Reflectance spectra of AhS 91A are dark (reflectance ~0.04–0.05) and relatively featureless in VNIR, and have an ~2.7 μm absorption band due to OH − in phyllosilicates. Spectral modeling, using mixtures of laboratory VNIR reflectance spectra of AhS stones to fit the F‐type spectrum of the asteroid, suggests that 2008 TC3 consisted mainly of ureilitic and AhS 91A‐like materials, with as much as 40–70% of the latter, and <10% of OC, EC, and other meteorite types. The bulk density of AhS 91A (2.35 ± 0.05 g cm −3 ) is lower than bulk densities of other AhS stones, and closer to estimates for the asteroid (~1.7–2.2 g cm −3 ). Its porosity (36%) is near the low end of estimates for the asteroid (33–50%), suggesting significant macroporosity. The textures of AhS 91A and AhS 671 (finely comminuted clasts of disparate materials intimately mixed) support formation of 2008 TC3 in a regolith environment. AhS 91A and AhS 671 could represent a volume of regolith formed when a CC‐like body impacted into already well‐gardened ureilitic + impactor‐derived debris. AhS 91A bulk samples do not show a solar wind component, so they represent subsurface layers. AhS 91A has a lower cosmic ray exposure (CRE) age (~5–9 Ma) than previously studied AhS stones (11–22 Ma). The spread in CRE ages argues for irradiation in a regolith environment. AhS 91A and AhS 671 show that ureilitic asteroids could have detectable ~2.7 μm absorption bands.